Horizon scanning for alien predatory crabs: insights from South Africa. Issue 2 (3rd April 2019) - Swart, C; Robinson, TB
Abstract : Due to the presence of few dominant predators on South African rocky shores, this coastline could be vulnerable to invasion by predatory crabs. This study applied horizon scanning to create an ordered watch list of alien crab species that could establish along this coastline under present-day and future temperature scenarios. This was done by: (i) identifying the species with both an invasion history and a possible pathway to South Africa; (ii) comparing the temperature ranges of the species' native and introduced distributions to those of each of the four South African ecoregions; and (iii) ranking the species based on their potential ecological impacts. Of the 56 alien predatory crab species known worldwide, 28 species have pathways to South Africa. Incompatible temperature ranges excluded only two species from each ecoregion. Negative ecological impacts in their invaded ranges placed Japanese shore crab Hemigrapsus sanguineus, brush-clawed shore crab H. takanoi and Chinese mitten crab Eriocheir sinensis at the top of the watch list. This study highlights that many alien crab species have the potential to reach South Africa, with most likely to survive. This watch list should be used to support targeted monitoring and so facilitate early detection of these species, should they reach South Africa.